2016
DOI: 10.5817/sp2016-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perception of Their Involvement in Schooling Activities: A Case Study from Rural Secondary Schools in Bangladesh

Abstract: The primary purpose of this study was to explore parents' perceptions of their involvement in their children's education. This study was conducted in secondary schools in a rural area of Bangladesh. People from this area mostly have low literacy and income rates. A qualitative case study research design was used. Five parents from five different schools in the rural context were interviewed. The findings from this study show that parents are not comfortable approaching the school and many parents do not consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Also, studies conducted on 417 prospective teacher students at Cumhuriyet University Faculty of Education resulted that there was no gender influence on students' behavior or environmental thinking [13]. Besides, studies on prospective students confirmed that that gender was not a factor that affects students' knowledge, awareness, attitudes, behaviors, and perceptions of the environment [16]. In addition to the above studies that support the researchers' findings, several studies showed different results.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Also, studies conducted on 417 prospective teacher students at Cumhuriyet University Faculty of Education resulted that there was no gender influence on students' behavior or environmental thinking [13]. Besides, studies on prospective students confirmed that that gender was not a factor that affects students' knowledge, awareness, attitudes, behaviors, and perceptions of the environment [16]. In addition to the above studies that support the researchers' findings, several studies showed different results.…”
Section: Discussionmentioning
confidence: 71%
“…Research on the influence of gender on literacy has been conducted in several countries such as Malaysia, Turkey, Nigeria, Iran, Taiwan, and Brazil. Some of the results showed that gender did not effect on environmental literacy [1] [11]- [16]. However, on the other hand, the other results showed different things in which gender positively affects environmental literacy [4], [17]- [23].…”
Section: Introductionmentioning
confidence: 99%
“…Hasnat's (2017) inquiry is part of a wider doctoral study of parental engagement in rural schools in Bangladesh, in which he interviewed, and walked with, a range of stakeholders: parents, students, teachers, head teachers and school management committee members. Some of the findings of his wider research, particularly the need for and the obstacles to engagement, have been reported elsewhere (Greenwood & Hasnat, 2017;Hasnat, 2016). Here the focus is on the changes one principal has made for his school.…”
Section: Methodological and Conceptual Framework: Walking And Talkingmentioning
confidence: 85%
“…According to earlier research findings, the bond between parents and their children is a reliable predictor of rising academic success ( Hussain et al., 2021 ). Hasnat (2016) , Hibi and Assadi (2021) noted that for education to be a continuous process and to materialize into behaviour, parents' active involvement should be present as a cornerstone for the encouragement of their children’s academic success and the establishment of the value system. According to the study’s findings, due to the TPLF violence severe economic toll on parents although they are prioritizing their economic pursuits over ensuring that their children are receiving a quality education.…”
Section: Discussionmentioning
confidence: 99%